IDENTIFIKASI KOMPETENSI MAHASISWA PENDIDIKAN KIMIA DALAM MENYELESAIKAN TUGAS PROYEK MENGGUNAKAN PENDEKATAN SELF-REGULATED LEARNING - Wa Hasriani; Rahmanpiu Rahmanpiu; Muh. Alim Marhadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
An interesting aspect of this study is that chemistry education students were able to complete project assignments involving the production of Virgin Coconut Oil (VCO), VCO soap, and VCO-ginger shampoo, even though they had never previously encountered real-world problems that needed to be solved through Project-Based Learning. The purpose of this research was to identify the learning strategies applied by chemistry education students in completing project assignments in the Technology of Chemistry Handicraft course. This research employed a descriptive survey method involving 45 students enrolled in the course during the 2024/2025 academic year. Data were collected through questionnaires and interviews, referring to the Self-Regulated Learning (SRL) framework, and analyzed using quantitative descriptive techniques. The results revealed that students’ learning strategies based on Self-Regulated Learning were categorized as very high, with an average score of 87.4% across three main dimensions. In the planning stage, students demonstrated the ability to design tasks, manage time, and divide roles within groups, achieving an average score of 89.6%. The implementation stage indicated strong collaboration skills and the effective use of technology, with a score of 86.5%. The evaluation stage, which included reflection and revision of project outcomes, reached 86%. Overall, students demonstrated the ability to plan their work, collaborate in groups, utilize technology, and reflect on their project outcomes, such as the production of VCO, VCO soap, and VCO-ginger shampoo. These findings indicate that Self-Regulated Learning skills help students become more independent, focused, and effective in completing project-based assignments. ABSTRAKHal yang menarik dalam penelitian ini adalah mahasiswa pendidikan kimia dapat menyelesaikan tugas proyek pembuatan Virgin Coconut Oil (VCO), Sabun VCO dan Shampo VCO-jahe tetapi dalam perkuiahan maupun di laboratorium mereka belum pernah dihadapkan pada masalah nyata yang harus di pecahkan melalui pembelajaran berbasis proyek. Tujuan penelitian ini adalah untuk mengidentifikasi strategi belajar yang diterapkan mahasiswa Pendidikan Kimia dalam menyelesaikan tugas proyek pada mata kuliah Teknologi Prakarya Kimia. Penelitian ini merupakan survei deskriptif dengan melibatkan 45 mahasiswa yang memprogram mata kuliah Teknologi Prakarya kimia tahun 2024/2025. Data dikumpulkan menggunakan kuesioner dan wawancara dengan mengacu pada strategi belajar Self-Regulated Learning. Data dianalisis menggunakan teknik deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa strategi belajar mahasiswa menggunakan Self-Regulated Learning termasuk dalam kategori sangat tinggi dengan rata-rata 87,4% pada ketiga dimensi. Pada tahap perencanaan, mahasiswa mampu merencanakan tugas, mengatur waktu, serta melakukan pembagian peran dalam kelompok dengan rata-rata 89,6%. Tahap pelaksanaan menunjukkan kemampuan kolaborasi dan pemanfaatan teknologi sebesar 86,5%. Tahap evaluasi meliputi kegiatan refleksi dan revisi hasil proyek dengan capaian 86%. Mahasiswa mampu merencanakan pekerjaan, bekerja sama dalam kelompok, memanfaatkan teknologi, serta melakukan refleksi terhadap hasil proyek seperti pembuatan Virgin Coconut Oil (VCO), sabun VCO dan sampo VCO-jahe. Hasil ini menunjukkan bahwa kemampuan regulasi diri dalam belajar membantu mahasiswa menjadi lebih mandiri, terarah, dan efektif dalam menyelesaikan tugas proyek.